Deregulated expression of c-Myc in a translocation-negative plasmacytoma on extrachromosomal elements that carry IgH and myc genes - Wiener, Francis (National Academy of Sciences, 1999)
The induced expression of c-Myc in plasmacytomas in BALB/c mice is regularly associated with nonrandom chromosomal translocations that juxtapose the c-myc gene to one of the Ig loci on chromosome 12 (IgH), 6 (IgK), or 16 (IgL). The DCPC21 plasmacytoma belongs to a small group of plasmacytomas that are unusual in that they appear to be translocation-negative. In this paper, we show the absence of any c-myc-activating chromosomal translocation for the DCPC21 by using fluorescent in situ hybridization, chromosome painting, and spectral karyotyping. We find that DCPC21 harbors c-myc and IgH genes on extrachromosomal elements (EEs) from which c-myc is transcribed, as shown by c-myc mRNA tracks and extrachromosomal gene transfer experiments. The transcriptional activity of these EEs is supported further by the presence of the transcription-associated phosphorylation of histone H3 (H3P) on the EEs. Thus, our data suggest that in this plasmacytoma, c-Myc expression is achieved by an alternative mechanism. The expression of the c-Myc oncoprotein is initiated outside the chromosomal locations of the c-myc gene, i.e., from EEs, which can be considered functional genetic units. Our data also imply that other “translocation-negative” experimental and human tumors with fusion transcripts or oncogenic activation may indeed carry translocation(s), however, in an extrachromosomal form.